Regional Labor Market Adjustments in the United States and Europe - Dao, Mai.; Furceri, Davide; Loungani, Prakash (Washington, D.C. : International Monetary Fund, 2014)
We examine patterns of regional adjustments to shocks in the US during the past 40 years. Using state-level data, we estimate the dynamic response of regional employment, unemployment, participation rates and net migration to state-relative labor demand shocks. We find that (i) the long-run effect of a state-specific shock on the state employment level has decreased over time, suggesting less overall net migration in response to a regional shock, (ii) the role of the participation rate as absorber of regional shocks has increased, (iii) the response of net migration to regional shocks is stronger, while that of relative unemployment is weaker during aggregate downturns, and (iv) the change in the response intensity of migration is related to the declining trend in regional dispersion of labor market conditions. Finally, using regional data for a set of 21 European countries, we show that while the short-term response of participation rates to labor demand shocks is typically larger in Europe than in the US, the immediate response of net migration in Europe has increased over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet